Pengaruh Kemandirian Belajar Dan Lingkungan Teman Sekelas Mahasiswa Terhadap Minat Belajar Mata Kuliah Sejarah Pemikiran Ekonomi - Meriza, Mica Siar; Firmansyah, Deyren; Aurel, Elsa; Situmorang, Eva; Leonard, Penus (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to examine how students' interest in the History of Economic Thought course is impacted by their peer environment and level of learning independence 33 students serving as samples for this research, which employed a purposeful sampling technique. and a quantitative approach with multiple linear regression. With t-values of 3.024 (p = 0.007) and 2.093 (p = 0.049), respectively, the study results show that learning independence (X1) and peer environment (X2) have a substantial partial influence on learning interest. With an F-value of 8.606 (p = 0.002), the simultaneous F-test demonstrates that both independent factors have a substantial impact on students' learning interest. With a coefficient of determination (R2) of 0.409, learning independence and peer environment account for 40.9% of the variation in learning interest, whereas other factors outside the model account for 59.1%. These results highlight how crucial learning autonomy and a positive social environment are for raising students' motivation to study.